2016
DOI: 10.1097/wad.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Phenotypes and Late-Life Dementia Risk

Abstract: Background Mendelian Randomization (MR) studies have reported that type 2 diabetes (T2D) was not associated with Alzheimer's Disease (AD). We adopted a modified, mechanism-specific MR design to explore this surprising result. Methods Using inverse-variance weighted MR analysis, we evaluated the association between T2D and AD using data from 39 single nucleotide polymorphisms (SNPs) significantly associated to T2D in DIAbetes Genetics Replication And Meta-analysis (DIAGRAM) and the corresponding associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
(40 reference statements)
4
28
0
Order By: Relevance
“…Two studies [ 12, 21 ] examined the causal relationship between type 2 diabetes (T2D) or related phenotypes and odds of AD using the International Genomics of Alzheimer’s Project (IGAP) GWAS results. One of these studies [ 21 ] also investigated the link with dementia probability in the Health and Retirement Study (HRS). Although they selected different sets of SNPs for the T2D GRS (49 [ 12 ] versus 39 [ 21 ] SNPs), neither study [ 12, 21 ] found a significant association with T2D.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies [ 12, 21 ] examined the causal relationship between type 2 diabetes (T2D) or related phenotypes and odds of AD using the International Genomics of Alzheimer’s Project (IGAP) GWAS results. One of these studies [ 21 ] also investigated the link with dementia probability in the Health and Retirement Study (HRS). Although they selected different sets of SNPs for the T2D GRS (49 [ 12 ] versus 39 [ 21 ] SNPs), neither study [ 12, 21 ] found a significant association with T2D.…”
Section: Resultsmentioning
confidence: 99%
“…One of these studies [ 21 ] also investigated the link with dementia probability in the Health and Retirement Study (HRS). Although they selected different sets of SNPs for the T2D GRS (49 [ 12 ] versus 39 [ 21 ] SNPs), neither study [ 12, 21 ] found a significant association with T2D. There was also little evidence to support the relationship with T2D related phenotypes, as the nominally significant finding by Walter and colleagues [ 21 ] for insulin sensitivity did not survive Bonferroni multiple testing correction ( p = 0.08).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported null associations between genetically-predicted body mass index with LOAD 33 . Likewise, variants encoding Type-2 diabetes were also unrelated to LOAD 34 .…”
Section: Discussionmentioning
confidence: 96%
“…However, in a follow-up MR study that examined single nucleotide polymorphisms independently according to their specific biological mechanism, Alzheimer’s disease dementia risk correlated negatively with insulin sensitivity only (31), a finding that is not surprising given the wealth of literature that connects insulin dysfunction with Alzheimer’s disease dementia–specific neuropathological changes. In addition, a recent examination of genome-wide association study data found significant overlap between single-nucleotide polymorphisms (SNPs) associated with type 2 diabetes and Alzheimer’s disease, providing initial evidence that the two diseases may indeed share genetic risk.…”
Section: Toward a Precision Medicine Model For Dementia: Type 2 Diabementioning
confidence: 99%